2005
DOI: 10.1007/s11179-005-0050-5
|View full text |Cite
|
Sign up to set email alerts
|

Byssus of the Green-Lipped Mussel Perna viridis (Linnaeus) as a Biomonitoring Material for Zn

Abstract: Recently, Yap et al. (2003) suggested that the byssus of the green-lipped mussel Perna viridis can be a biomonitoring material for Zn although further validation is required. In this work, we did a simple correlation study between Zn concentrations in the byssus (and soft tissue) and in different geochemical fractions of the sediment. A significant ( P < 0.01) Pearson's correlation coefficient ( R = 0.84) between the Zn concentrations in the byssus and soft tissue indicated that the Zn level in the byssus is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Although many trace elements, being micronutrients, are necessary for the normal physiological activity of aquatic organisms, many of them can be concentrated in excess of physiological requirements in soft tissues and become toxic (Briffa et The content of Zn in byssus depends on its concentration in seawater and also in soft tissues as it can be extracted from the mussel body into byssus. Yap et al (2005) noticed that if large amounts of heavy metals are accumulated in soft tissues of M. edulis, then the metals are transferred to byssus in almost equal proportions, and the same pattern was noted in the present research with respect to M. galloprovincialis (Table 1).…”
Section: Human Health Risk Assessmentsupporting
confidence: 88%
“…Although many trace elements, being micronutrients, are necessary for the normal physiological activity of aquatic organisms, many of them can be concentrated in excess of physiological requirements in soft tissues and become toxic (Briffa et The content of Zn in byssus depends on its concentration in seawater and also in soft tissues as it can be extracted from the mussel body into byssus. Yap et al (2005) noticed that if large amounts of heavy metals are accumulated in soft tissues of M. edulis, then the metals are transferred to byssus in almost equal proportions, and the same pattern was noted in the present research with respect to M. galloprovincialis (Table 1).…”
Section: Human Health Risk Assessmentsupporting
confidence: 88%
“…Active elimination of metals from the soft tissues to byssus by a possible 'detoxification' mechanism has even been considered [2]. Thus, the reliability of the use of mytilid byssus as a marker of trace metal pollutants was intensively investigated in the last two decades, resulting in some promising conclusions [4][5][6][7][8][9][10][11][12][13]. More recently, it has been experimentally proved that Fe ions are incorporated in the Mytilus galloprovincialis thread cuticle during the secretion of a new thread and not by direct absorption from the surrounding waters [14].…”
Section: Introductionmentioning
confidence: 99%
“…8. This could be due to its role as an excretion route for Fe, Cu, and Ni as proposed in P. viridis for Zn (Yap et al 2005). This indicated that byssus had different mechanisms of metal accumulation when compared to other soft tissues.…”
Section: Methodsmentioning
confidence: 92%